Pengaruh Motivasi Auditor dan Kompleksitas Tugas terhadap Kinerja Auditor Pemerintah Daerah: Studi pada Inspektorat Aceh - Laisa Liza (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of auditor motivation and task complexity on the performance of government auditors. Auditor motivation is considered a crucial factor that can drive work efficiency and effectiveness, while task complexity contributes to determining an auditor's ability to optimally complete their tasks. This research was conducted on employees of the Aceh Inspectorate, encompassing 82 individuals from various positions, including Inspectors, Secretaries, Assistant Inspectors, functional auditor officials, and other staff. The study employed a quantitative approach with a census method, where the entire population was used as the research sample. To test the hypotheses, Structural Equation Modeling (SEM) was utilized, allowing simultaneous and in-depth analysis of variable relationships. SEM was chosen for its ability to test causal relationships and provide accurate estimations regarding the influence of variables in the study. The findings indicate that auditor motivation has a direct and significant effect on auditor performance, with a greater contribution than task complexity. High motivation has been proven to enhance the efficiency and effectiveness of auditors' work. Task complexity also has a significant impact, though its contribution is moderate (value of 0.417). However, the study also revealed that other factors, such as integrity, professionalism, and auditor independence, influence auditor performance, even though they were not the primary focus of the research. This study emphasizes the importance of enhancing auditor motivation and managing task complexity, as well as integrating other factors into further analyses to provide a holistic understanding of the factors affecting the performance of government auditors.